The Use of Four-Square Technique to Improve Students’ Writing Ability - Yulianti Yunus; Syarifuddin Dollah; Munir Munir (Fakultas Sastra - Universitas Muslim Indonesia, 2021)
This study employed a quasi-experimental approach that aimed to find out the extent of the improvement students' writing ability by using the Four-Square Technique on the descriptive text at students X SMAN 3 Takalar. the authors took 53 samples, 28 students as the experimental group and 25 students as the control group. The study data was obtained by giving a pre-test and post-test and analyzed by using the Dependent Sample T- Test. The result of the data showed that students' writing ability improved. It was proved from score result of tobs (16,673) which was higher than t-table (2.052) and sig. P (0.05) was higher than sig.score (0.000). Students' writing ability improve by 0.1% after using the Four-Square Technique from pre-test mean score was 65.07 and the post-test mean score was 75.14. So, it can be concluded that using Four-Square Technique can improve students' writing ability in writing a descriptive text at students X SMAN 3 Takalar. By using it, students showed that they can be motivated in writing, students more easily generate and organize their ideas into a text so that students’ writing was more organized also easy to understand.